Radio Frequency Energy Harvesting - Mohd Farouk Bin Mohd Saad, Mohd Farouk (2010)
This project aims to come out with a system that able to exert some energy from radio waves that able to use by other electronics equipments. This device consists of three main parts to works which are, Radio Frequency Transducer, Power Management circuit, and the Energy Storage Device.